The role of splicing events in the inflammatory response of atherosclerosis: molecular mechanisms and modulation - Wang, Aolong; Wang, Chengzhi; Xuan, Bihan; Sun, Yanqin; Li, Bin; Zhao, Qifei; Yu, Rui; Wang, Xinlu; Zhu, Mingjun; Wei, Jingjing (Frontiers in Immunology, 2024)
Atherosclerosis is a chronic inflammatory disease characterized by persistent inflammatory responses throughout all stages of its progression. Modulating these inflammatory responses is a promising avenue for the development of cardiovascular disease therapies. Splicing events modulate gene expression and diversify protein functionality, exerting pivotal roles in the inflammatory mechanisms underlying atherosclerosis. These insights may provide novel opportunities for developing anti-inflammatory therapies for this disease. This article systematically discusses the diverse splice variants and how splicing events impact the inflammatory response in atherosclerosis via endothelial cells, macrophages, and vascular smooth muscle cells, highlighting their underlying molecular mechanisms and implications. Furthermore, this study summarizes clinical evidence supporting splicing-related molecules as diagnostic biomarkers and therapeutic targets in atherosclerosis. Lastly, we outline the current challenges and future research directions concerning splicing events and inflammatory responses in atherosclerosis. This offers a novel perspective and evidence for formulating new therapeutic strategies aimed at lowering the risk of atherosclerosis.